The Political Economy of Fulfilling the Minimum Essential Force: Contextual investigations of Idea Improvement in the Guard Business - Guntur Eko Saputro; Junindra Duha (International Journal of Artificial Intelligence Research, 2022)
This article investigates the effectiveness of policies in Fulfilling the Minimum Essential Force in Indonesia through Defense Budget Allocations based on Law Number 3 of 2002 concerning National Defense. One of the targets of the Indonesian Government in the defense sector is the independence of the defense industry to produce defense equipment without relying on other countries through the Minimum Essential Force (MEF). The fulfillment of the Minimum Essential Force (MEF) target is to reach 100 percent by the end of Minimum Essential Force (MEF) III by the end of 2024. But, Indonesia's defense budget for the 2009-2018 period is still below 1 percent of GDP, or below the average defense budget. ASEAN's countries. Our findings suggest that budgetary support is required from the Government to meet the Minimum Essential Force (MEF) by increasing the defense budget by at least 1.5 percent on the target